PENYERAPAN TENAGA KERJA OLEH SEKTOR PERTANIAN TAHUN 2016-2021 - Wiwi Sepriani; Yuliawati (Fakultas Ekonomi Universitas Samudra, 2022)
ABSTRACT Indonesia's economic growth rate contracted during the covid-19 pandemic, in 2019 the economic growth rate was still positive at 5.02% while in 2020 the growth rate decreased to a negative value of -2.07%. Too many layoffs will cause the unemployment rate to increase. The agricultural sector plays a role in absorbing labor and determining the number of workers that can be absorbed so as to reduce unemployment, especially forced unemployment during the pandemic. This study aims to determine the role of the agricultural sector in employment and its effect on poverty rates in Indonesia in 2016-2021. This study uses a descriptive analysis writing type. The secondary data comes from BPS, journals and other official reports, with 5 years of time series data. The data collection technique is the literature study technique. Analysis of the data used is by searching, collecting, reading, studying and reviewing library sources in order to achieve the research objectives. The agricultural sector has the largest role in absorbing labor than the industrial sector and trade services during the economic crisis due to the COVID-19 pandemic, amounting to 38,224,371 million people who work. Actions that must take to develop this sector need to be taken by the government so that it becomes a priority to be developed like other sectors. The role of the agricultural sector has a competitive value and contributes greatly to Indonesia's economic growth Key Word: Job absorption, unemployment, the role pf the farming sector